Phenotypic and Functional Responses of Human Decidua Basalis Mesenchymal Stem/Stromal Cells to Lipopolysaccharide of Gram-Negative Bacteria - Alshareef GH (Dove Medical Press, 2021)
Ghofran Hasan Alshareef,1 Afrah E Mohammed,1 Mohammed Abumaree2,3 ,† Yasser S Basmaeil2 1Biology Department, College of Science, Princess Nourah Bint Abdulrahman University, Riyadh, 84428, Saudi Arabia; 2Stem Cell & Regenerative Medicine Department, King Abdullah International Medical Research Center, King Saud bin Abdulaziz University for Health Sciences, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 3College of Science and Health Professions, King Saud bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, 11481, Saudi Arabia†Prof. Mohammed Abumaree passed away on 26.07.2019.Correspondence: Afrah E Mohammed; Yasser S BasmaeilStem Cell & Regenerative Medicine Department, King Abdullah International Medical Research Center, Ministry of National Guard Health Affairs, Riyadh, Saudi ArabiaTel +966 11 8011111 Ext: 94573Email AFAMohammed@pnu.edu.sa; basmaeily@ngha.med.saIntroduction: Human decidua basalis mesenchymal stem cells (DBMSCs) are potential therapeutics for the medication to cure inflammatory diseases, like atherosclerosis. The current study investigates the capacity of DBMSCs to stay alive and function in a harmful inflammatory environment induced by high levels of lipopolysaccharide (LPS).Methods: DBMSCs were exposed to different levels of LPS, and their viability and functional responses (proliferation, adhesion, and migration) were examined. Furthermore, DBMSCs’ expression of 84 genes associated with their functional activities in the presence of LPS was investigated.Results: Results indicated that LPS had no significant effect on DBMSCs’ adhesion, migration, and proliferation (24 h and 72 h) (p > 0.05). However, DBMSCs’ proliferation was significantly reduced at 10 μg/mL of LPS at 48 h (p < 0.05). In addition, inflammatory cytokines and receptors related to adhesion, proliferation, migration, and differentiation were significantly overexpressed when DBMSCs were treated with 10 μg/mL of LPS (p < 0.05).Conclusion: These results indicated that DBMSCs maintained their functional activities (proliferation, adhesion, and migration) in the presence of LPS as there was no variation between the treated DBMSCs and the control group. This study will lay the foundation for future preclinical and clinical studies to confirm the appropriateness of DBMSCs as a potential medication to cure inflammatory diseases, like atherosclerosis.Keywords: placenta, endothelial cells, proliferation, adhesion, migration, real-time PCR